(untitled) (Global Journal of Management and Business Research, 2020)
The service industry has always more challenging and competitive because customers are constantly demanding more services for less money. This has shifted organizations strategic plans and goals towards customer orientation and satisfaction. The importance of retaining existing customers and expanding business is paramount. Hence, efforts are laid by all the firms towards maintaining sound relationship with customers. This process is known as CRM. Customer Relationship Management or CRM is a customer oriented strategy for creating, maintaining and expanding customer relationships. It is a roadmap that identifies how a company can meet and exceed its customers’ needs. Taking this into cognizance, the present research has been conducted to examine the impact of customer relationship management practices on customer satisfaction as well as on customer loyalty in selected Jordanian banks. Data has been collected through structured questionnaires from 442 customers and analyzed with the application of multiple regression.